(untitled) - Dupayrat, Jacques (Paris, 1988)
This dictionary has been more particularly elaborated with the aim of gathering in the same work the maximum of keywords relating to the research-and industrial chemistry applied to the "Life science", that is in particular: pharmacy, pharmacology, biochemistry, toxicology, genetics, bioengineering, etc.
Keywords: Biochemistry,Biotechnology,English language; French